1996
DOI: 10.1007/bf00328791
|View full text |Cite
|
Sign up to set email alerts
|

Leaf 15N abundance of subarctic plants provides field evidence that ericoid, ectomycorrhizal and non-and arbuscular mycorrhizal species access different sources of soil nitrogen

Abstract: The natural abundance of the nitrogen isotope 15, δN, was analysed in leaves of 23 subarctic vascular plant species and two lichens from a tree-line heath at 450 m altitude and a fellfield at 1150 m altitude close to Abisko in N. Sweden, as well as in soil, rain and snow. The aim was to reveal if plant species with different types of mycorrhizal fungi also differ in their use of the various soil N sources. The dwarf shrubs and the shrubs, which in combination formed more than 65% of the total above-ground biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
244
3
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(272 citation statements)
references
References 38 publications
20
244
3
5
Order By: Relevance
“…This suggests either N-source differences in isotopic signature, or differences in the plantfungal system with respect to physiological processes that alter the isotopic signature of N (Nadelhoffer et al, 1996). Michelson et al (1996Michelson et al ( , 1998 argue that this pattern is most likely a function of differences in pool use rather than fractionation processes. If it is a function of differences in pool use, then it runs contrary to the pattern of higher isotopic enrichment for protein-users in the present study, and counter to the expected pattern of isotopic signature of labile soil N pools under low N conditions, i.e.…”
Section: Nitrogen Isotopes and Protein Usementioning
confidence: 99%
“…This suggests either N-source differences in isotopic signature, or differences in the plantfungal system with respect to physiological processes that alter the isotopic signature of N (Nadelhoffer et al, 1996). Michelson et al (1996Michelson et al ( , 1998 argue that this pattern is most likely a function of differences in pool use rather than fractionation processes. If it is a function of differences in pool use, then it runs contrary to the pattern of higher isotopic enrichment for protein-users in the present study, and counter to the expected pattern of isotopic signature of labile soil N pools under low N conditions, i.e.…”
Section: Nitrogen Isotopes and Protein Usementioning
confidence: 99%
“…In a few studies, natural abundance of 15 N of soil and foliage has been used to identify areas with higher rates of nitrification (Garten 1993;Garten and Van Miegroet 1994;Emmett et al 1998). Several studies have suggested that among non-mycorrhizal plants, VA (vesicular-arbuscular) plants are generally higher than in 15 N than ectomycorrhizal plants (Michelsen et al 1996;Schimdt and Stewart 1997). Hobbie et al (2000) reported that foliar N concentration and δ 15 N were correlated at nitrogen limited sites, and attributed this pattern to differences in plant and mycorrhizal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large proportion of total soil N and P is tied up in the microbial biomass (Cheng & Virginia, 1993 ;Jonasson et al, 1996a ;Michelsen et al, 1996b). In the light of the potential effects of CO # enhancement and warming on microbial biomass and the possible consequences for tundra ecosystem function (Nadelhoffer et al, 1992), it is urgent to integrate investigations of plant and microbial responses to environmental changes.…”
mentioning
confidence: 99%